(untitled) (Homoeopathy for All, 2021)
Psoriasis is a chronic dermatological condition characterized by presence of papules and plaques with well defined erythematous lesion with large, silvery scales.1 It is a non contagious, autoimmune, inflammatory skin disorder. 2,3In 10- 30% of people, it has been observed that more than one member in the family will have history of psoriasis.4 Psoriasis is the most common skin disease which affects 1-3% in overall population. It can affect any age, but usually it is observed in the 2nd,3rd and middle of 5th decade of life. 1,5,60.44% to 2.2% of people are affected by psoriasis approximately among South Indian population.7 Both sexes are affected equally with mean age of onset ranging from 20 to 39 years with 2 weeks to 9 years of remissions.